2014
DOI: 10.1002/chem.201402070
|View full text |Cite
|
Sign up to set email alerts
|

Direct Metal‐Catalyzed Regioselective Functionalization of Enamides

Abstract: Enamides are stable enamine surrogates and provide key intermediates for the synthesis of small but complex nitrogen-containing compounds. Metal-catalyzed regioselective functionalization of enamides provides a rapid method to synthesize useful nitrogen containing heterocycles. This review discloses the recent progress made in the development of the C-H functionalization of enamides involving efficient and atom-economical routes. Syntheses of different heterocycles are classified based on the site reactivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(43 citation statements)
references
References 114 publications
0
42
0
Order By: Relevance
“…[12][13][14] Enecarbamates have been the center of intense interest over the past few years [15,16] and led us to explore the reactivity of 5 (Scheme 2). [12][13][14] Enecarbamates have been the center of intense interest over the past few years [15,16] and led us to explore the reactivity of 5 (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Enecarbamates have been the center of intense interest over the past few years [15,16] and led us to explore the reactivity of 5 (Scheme 2). [12][13][14] Enecarbamates have been the center of intense interest over the past few years [15,16] and led us to explore the reactivity of 5 (Scheme 2).…”
mentioning
confidence: 99%
“…[8] Thef ollowing mechanism can be proposed. [12][13][14] Enecarbamates have been the center of intense interest over the past few years [15,16] and led us to explore the reactivity of 5 (Scheme 2). [5d, 9, 10] Ac hairlike transition state [a] The reactions were carried out by addition of asolution of CBr 4 (0.56 mmol, 2.8 equiv) in CH 2 Cl 2 (0.5 mL) to amixture of 1 (0.2 mmol), polymer-supported phosphine (2.5 equiv),and Et 3 N(0.4 mmol, 2equiv) in dry CH 2 Cl 2 (2 mL).…”
mentioning
confidence: 99%
“…[2] In contrast, the analogous CÀHf unctionalization of azaallyl derivatives remains largely unexplored. Given that allylic amines and enamines [3] are valuable building blocks and are prevalent in bioactive compounds [4] (e.g.n aftifine [4d] and flunarizine [4e] ), the C À Hf unctionalization of azaallyl systems has significant untapped potential.Early studies with azaallyl palladium intermediates were reported by ODonnell et al [5] and involved relatively sensitive hemiaminal precursors (Scheme 1A). In 2015, Tr ost et al [6] reported the use of readily available N-allyl imines in oxidative C À Hf unctionalization reactions in the presence of 2,6-dimethylbenzoquinone (Scheme 1B).…”
mentioning
confidence: 99%
“…[2] In contrast, the analogous CÀHf unctionalization of azaallyl derivatives remains largely unexplored. Given that allylic amines and enamines [3] are valuable building blocks and are prevalent in bioactive compounds [4] (e.g.n aftifine [4d] and flunarizine [4e] ), the C À Hf unctionalization of azaallyl systems has significant untapped potential.…”
mentioning
confidence: 99%
“…No erosion of the stereochemical integrity of the starting alkynol was observed for 5a-h (Table 1), thus demonstrating that the [3,3]-sigmatropic rearrangement occurred with complete 1,3-chirality transfer.In the case of 5i,partial loss of chiral information could result from the participation of ac ationic phenonium intermediate which is trapped by S N 2' addition of the cyanate anion. [12][13][14] Enecarbamates have been the center of intense interest over the past few years [15,16] and led us to explore the reactivity of 5 (Scheme 2). Hydrogenation with H 2 in the presence of Pd/C and methylation mediated by silver oxide afforded 6 (90 %) and 7 (95 %), respectively.T reatment with 1 m HCl in THF caused ring opening to provide the aldehyde 8,a nd vicinal dioxygenation using PhI(OAc) 2 occurred in high yield to afford 9a as the major isomer.…”
mentioning
confidence: 99%